Limitations of Current Polarization for Lowering the Detection Limit of Potentiometric Polymeric Membrane Sensors - Hofler, L.; Bedlechowicz, I.; Vigassy, T.; Gyursanyi, R.; Bakker, Eric; Pretsch, E. (American Chemical Society, 2009)
Ion fluxes across polymeric ion-selective membranes are a decisive parameter dictating the lower detection limit of potentiometric ion sensors. An applied current was earlier proposed to counteract such fluxes and reduce the detection limit to ultratrace levels. So far, however, the method has not been used in practical situations since the correct current amplitude requires prior knowledge of the sample composition. This paper explores the use of the stir effect to evaluate the optimal current by theory and experiments. It is shown that the traditionally used steady-state model assuming a uniform distribution of ion exchanger in the membrane, fixed with time, violates the electroneutrality condition. A modified steady-state model is introduced that allows for a concentration tilt of the ion exchanger and predicts that a stir effect can indeed be utilized to find the optimal current. Ideally, by choosingthe optimal current and very long measurement times, the thermodynamic detection limit might be obtained. However, in practice the stir effect declines at low concentrations and the conditions are far from steady state. Therefore, the improvement of the lower detection limit achievable by galvanostatic control is only about 1 order of magnitude. A numerical finite-difference approximation is shown to trace the experimental potential responses of silver-selective electrodes well and to reproduce the stireffect adequately, even for different conditioning protocols. The stir effect is successfully used to improve the detection limit of electrodes with ill-optimized inner solutions; however, significant improvements beyond what is commonly feasible by chemical optimization does not seem to be easily achievable. The results indicate that with conventional membranes the possibility of improving the detection limit by current polarization is much more limited than assumed so far.